Towards Disseminating Kartvelology in foreign scholarly circles - Nino Chakunashvili, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
The Center for Kartvelian (Georgian) Studies has functioned for over 15 years at Tbilisi State University, continuously serving the spread of Kartvelological activity abroad and getting young foreign specialists interested in Georgian Studies.